Association of Risk Factors with Breast Cancer in Libyan Women - Ameigaal, Samira. D.; Ageel, Ahmed. A; Abdoarahem, Mostafa. O. (Al-Mukhtar Journal of Sciences, 2020)
Breast cancer (BC) is the most common cancer among Libyan females. There are many important risk factors for BC in different populations as suggested by epidemiological studies. BC is an etiologically complex disease affected by genetic and other environmental factors, which include gender, age, previous breast cancer, body mass index, menopausal status, postmenopausal hormonal therapy, reproductive factor, alcohol consumption, smoking and breastfeeding. The aim of this study was to investigate if there is an association between risk factors and breast cancer among Libyan females. Data were collected by using questioners for 38 cases with breast cancer from Tripoli Medical Center and 100 controls from March 2016 to February 2017. The results showed that risk of breast cancer was associated with age, the mean ages (± SD) of the case and control groups were 46.7 ± 15.6 and 38.8 ± 19.1 respectively, age at the first birth (P=0.036), family history with first-degree relative percentage of the cases and control groups were 21% and 4% and second-degree relatives were 10.5% and 13% respectively with statistical difference (P=0.042) and menopausal status (P=0.002). The risk decreased with breastfeeding (P=0.033). No association was observed between passive smoking (P=0.363) and the number of pregnancies and births (P=0.402). Data from this study indicated that there were some factors associated with breast cancer among Libyan females including age, age at the first pregnancy, family history and menopausal status.